Realism reader - Elman, Colin; Jensen, Michael (Milton Park, Abingdon, Oxon ; New York : Routledge, 2014)
'The Realism Reader provides broad coverage of a centrally important tradition in the study of foreign policy and international politics'--
Contents note continued: China's unpeaceful rise / John J. Mearsheimer -- The tragedy of offensive realism: classical realism and the rise of China / Jonathan Kirshner -- 15.Is realism heading in the right direction? -- The realist paradigm and degenerative versus progressive research programs: an appraisal of neotraditional research on Waltz's balancing proposition / John A. Vasquez -- Evaluating theories / Kenneth N. Waltz -- The progressive power of realism / Stephen M. Walt -- Is anybody still a realist? / Andrew Moravcsik -- Correspondence: brother, can you spare a paradigm? / Andrew Moravcsik.
Includes bibliographical references and index.
Keywords: Realism -- Political aspects; International relations -- Philosophy; World politics